Pyoderma gangrenosum after caesarean section: a case report - Schuitemaker Nico; Banga Franyke; Meijer Piet (BMC, 2006)
Abstract Background Pyoderma gangrenosum is a rare ulcerative skin disease. The diagnosis is based on clinical features and excluding other causes of skin ulcers, as it does not have characteristic histopathology or laboratory findings. The etiology is poorly understood. Lesions can develop spontaneously, after surgery or after trauma. Case presentation We present the case of a 32-year-old woman with ulcerative wound defect after caesarean section. The wound was not healing despite standard wound care and antibiotic treatment. Pyoderma gangrenosum was diagnosed and after high dose corticosteroids wound healing started. Conclusion Early diagnosis and subsequent treatment of pyoderma gangrenosum are crucial for limiting scar tissue. Diagnosis of pyoderma gangrenosum could easily be missed since gynaecologists are rarely confronted with this disorder.